The letters of T.S. Eliot. - Eliot, T. S. (Thomas Stearns), 1888-1965 (Yale University Press, 2011)
Volume One: 18981922presents some 1,400 letters encompassing the years of Eliot's childhood in St. Louis, Missouri, through 1922, by which time the poet had settled in England, married his first wife, and publishedThe Waste Land. Since the first publication of this volume in 1988, many new materials from British and American sources have come to light. More than two hundred of these newly discovered letters are now included, filling crucial gaps in the record and shedding new light on Eliot's activities in London during and after the First World War. Volume Two: 19231925covers the early years of Eliot's editorship ofThe Criterion, publication ofThe Hollow Men, and his developing thought about poetry and poetics. The volume offers 1,400 letters, charting Eliot's journey toward conversion to the Anglican faith, as well as his transformation from banker to publisher and his appointment as director of the new publishing house Faber & Gwyer. The prolific and various correspondence of this volume testifies to Eliot's growing influence as cultural commentator and editor.